Positive electrode material and preparation method thereof, positive electrode plate, battery and electric device

By preparing the cathode material with the chemical formula of LiNixCoyMnzMiO2 and controlling the half-maximum width value of its key crystal surface, the shortcomings of the existing lithium-ion battery cathode materials in terms of high energy density and stability are solved, and excellent battery performance is achieved.

CN119812307APending Publication Date: 2025-04-11ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510003256.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have shortcomings in terms of high energy density and stability, especially in the field of new energy vehicles, and the demand for higher range and battery performance has not been fully met.

Method used

The positive electrode material with the chemical formula of LiNixCoyMnzMiO2 is used to prepare a stable crystal structure by controlling the half-maximum width of its (003), (006), (012), (101), (104), (018) and (110) crystal planes. The preparation method of the material includes multiple sintering and crushing mixing treatments to control the grain growth process.

Benefits of technology

It achieves excellent performance of short-term and long-term electrical properties of the positive electrode material, avoids the disadvantage that traditional half-maximum width ratio constraints cannot feedback the overall situation of the crystal structure, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812307A_ABST
    Figure CN119812307A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive electrode plate, a battery and an electric device. The chemical formula of the positive electrode material is LiNixCoyMnzMiO2, x is greater than or equal to 0, y is greater than or equal to 0, Z is greater than or equal to 0, i is greater than or equal to 0, x + y + z + i = 1, and M comprises one or more of Al, Zr, Ti, Mg, Sr, W, Y, Nb, Ca, Mo, B, F, Ge, Sn, Ce and Ta; the value Dn of the half-peak width of the (003) crystal face and the value Dn of the half-peak width of the (006) crystal face of the positive electrode material respectively meet the formula: 0.01 n + 0.067 > = Dn > = 0.053, and the value of n is 1 or 2; the values Dn of the half-peak widths of the crystal face (012), the crystal face (101), the crystal face (104), the crystal face (018) and the crystal face (110) of the positive electrode material respectively meet the formula that Dn is greater than or equal to 0.01 n + 0.067 and greater than or equal to 0.01 n + 0.023, and n is an integer from 3 to 7. The preparation method of the positive electrode material is used for preparing the positive electrode material, the positive electrode plate comprises the positive electrode material, the battery comprises the positive electrode plate containing the positive electrode material, and the electric device comprises the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material chemistry, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] Lithium-ion batteries are a very common type of battery in mobile devices, electric vehicles, and energy storage, especially in the field of new energy vehicles, where there is a high demand for lithium-ion batteries. In order to pursue a longer driving range, battery capacity and energy density are also getting higher and higher. High-end cars often use lithium nickel cobalt manganese oxide materials with higher energy density as positive electrodes. Among them, lithium ions are charged and discharged by being released and embedded in the transition metal oxide layer. Based on this, the orderliness and structural stability of the layered structure of synthetic lithium nickel cobalt manganese oxide play a key role in the electrical properties of the material. Summary of the invention

[0003] In order to improve battery performance, the embodiments of the present application provide positive electrode materials and preparation methods thereof, positive electrode sheets, batteries and electrical devices.

[0004] The present invention provides a positive electrode material, the chemical formula of which is LiNi x Co y Mn z M i O 2 ; wherein, x≥0, y≥0, Z≥0, i≥0, and x+y+z+i=1, M includes one or more of Al, Zr, Ti, Mg, Sr, W, Y, Nb, Ca, Mo, B, F, Ge, Sn, Ce, and Ta; in the positive electrode material, the half-peak width of the (003) crystal plane and the (006) crystal plane of the positive electrode material is D n Each satisfies the formula 0.01n+0.067≥D n ≥0.053, the value of n is 1 or 2, wherein the value of n is 1 when corresponding to the (003) crystal plane of the positive electrode material, and the value of n is 2 when corresponding to the (006) crystal plane of the positive electrode material; in the positive electrode material, the half-peak width of the (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane of the positive electrode material is D n Each satisfies the formula 0.01n+0.067≥D n ≥0.01n+0.023, the value of n is 3 to 7 and n is an integer, wherein the value of n is 3 when corresponding to the (012) crystal plane of the positive electrode material, the value of n is 4 when corresponding to the (101) crystal plane of the positive electrode material, the value of n is 5 when corresponding to the (104) crystal plane of the positive electrode material, the value of n is 6 when corresponding to the (018) crystal plane of the positive electrode material, and the value of n is 7 when corresponding to the (110) crystal plane of the positive electrode material.

[0005] Furthermore, in the positive electrode material provided in the embodiment of the present application, the half-widths of the (003) crystal plane, (006) crystal plane, (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane are simultaneously constrained. This constraint condition is different from the half-width ratio constraint condition, and can avoid the disadvantage that the aforementioned ratio constraint condition cannot provide feedback on the overall situation of the crystal structure. At the same time, the short-term and long-term electrical properties of the positive electrode material corresponding to the embodiment of the present application are excellent.

[0006] In one embodiment, the half-peak widths of the (003) and (006) crystal planes of the positive electrode material are D n Each satisfies the formula 0.01n+0.057≥D n ≥0.063, the half-peak widths of the (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane of the positive electrode material are D n Each satisfies the formula 0.01n+0.057≥D n ≥0.01n+0.033.

[0007] In one embodiment, the physicochemical indicators of the positive electrode material satisfy the relationship: 1.5≤D50 / (TD*SSA)≤3.5, wherein D50 represents the median particle size, TD represents the tap density, and SSA represents the specific surface area.

[0008] In one embodiment, the physicochemical indexes of the positive electrode material satisfy the relationship: 10.5≤pH / (Li / M)≤11.5, wherein pH represents the acidity and Li / M represents the lithium metal ratio.

[0009] The present application also provides a method for preparing a positive electrode material. The method for preparing a positive electrode material is used to prepare the positive electrode material as described in any one of the above embodiments. The method for preparing a positive electrode material comprises the following steps:

[0010] Mixing a hydroxide precursor, a lithium source and an additive containing an M element to obtain a first mixed material;

[0011] The first mixed material is subjected to a first sintering process, and after the sintering process, it is subjected to a crushing and mixing process to obtain a second mixed material;

[0012] The second mixed material is sintered for a second time, and after sintering, crushed and mixed to obtain a third mixed material;

[0013] The third mixed material is sintered for a third time, and the positive electrode material is obtained by post-sintering treatment.

[0014] Furthermore, the preparation method of the positive electrode material provided in the embodiment of the present application realizes the control of the grain growth process by controlling the sintering process, thereby obtaining a stable crystal structure in which the half-width of each crystal plane meets the requirements, and then obtaining the positive electrode material.

[0015] In one embodiment, during the first sintering process, the temperature is raised to the first platform temperature at a first heating rate, then kept at the temperature for a first time, and then naturally cooled to room temperature after the holding, and crushed and mixed to obtain the second mixed material;

[0016] During the second sintering process, the temperature is first increased to the second platform temperature at a second heating rate, then kept at the temperature for a second time, then increased to the third platform temperature at a third heating rate, then kept at the temperature for a third time, and after keeping at the temperature, the temperature is cooled to the first transition temperature at the first cooling rate, and then naturally cooled to room temperature, and crushed and mixed to obtain the third mixed material;

[0017] During the third sintering process, the temperature is raised to a fourth platform temperature at a fourth heating rate, then kept at the temperature for a fourth time, and then naturally cooled to room temperature, and crushed and mixed to obtain the positive electrode material.

[0018] In one embodiment, the first heating rate ranges from 2°C / min to 15°C / min, the first platform temperature ranges from 700°C to 820°C, and the first time ranges from 10 hours to 20 hours;

[0019] The second heating rate ranges from 2°C / min to 15°C / min, the second platform temperature is 700°C to 820°C, the second time is 3 hours to 10 hours, the third heating rate ranges from 2°C / min to 15°C / min, the third platform temperature is 830°C to 1000°C, the third time is 8 hours to 15 hours, the first cooling rate ranges from 2°C / min to 10°C / min, and the first transition temperature is less than 300°C;

[0020] The fourth heating rate ranges from 2°C / min to 15°C / min, the fourth platform temperature ranges from 300°C to 800°C, and the fourth time ranges from 5 hours to 20 hours.

[0021] In one embodiment, the lithium metal ratio Li / M in the first mixture is in the range of 0.6 to 0.9, and the lithium metal ratio Li / M in the second mixture is in the range of 1.0 to 1.1.

[0022] An embodiment of the present application also provides a positive electrode plate, which includes a positive electrode material, wherein the positive electrode material is the positive electrode material described in any one of the aforementioned embodiments, or the positive electrode material is prepared by the preparation method of the positive electrode material described in any one of the aforementioned embodiments.

[0023] An embodiment of the present application also provides a battery, which includes the positive electrode plate as described in the above embodiment.

[0024] The embodiment of the present application further provides an electricity-consuming device, which includes an electricity-consuming body and the battery as described in the above embodiment, wherein the battery is electrically connected to the electricity-consuming body.

[0025] Furthermore, the positive electrode plate, battery and electrical device provided in the embodiments of the present application all use the positive electrode material, and both the short-term and long-term electrical properties are excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram of a method for preparing a positive electrode material provided in an embodiment of the present application.

[0027] Figure 2 The graph shows the test results of the half-peak width of each crystal plane of the positive electrode materials of Examples 1 to 5 and Comparative Examples 1 to 2 of the present application after XRD testing.

[0028] The following specific implementation methods will further illustrate the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION

[0029] The following description will refer to the accompanying drawings to more fully describe the content of the present application. Shown in the accompanying drawings are exemplary embodiments of the present application. However, the present application can be implemented in many different forms and should not be construed as being limited to the exemplary embodiments set forth herein. These exemplary embodiments are provided to make the present application thorough and complete, and to fully convey the scope of the present application to those skilled in the art. Similar reference numerals represent identical or similar components.

[0030] The terms used herein are only used for the purpose of describing specific exemplary embodiments and are not intended to limit the present application. As used herein, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to also include the plural forms. In addition, when used herein, "including" and / or "comprising" and / or "having", integers, steps, operations, components and / or components, but do not exclude the existence or addition of one or more other features, regions, integers, steps, operations, components and / or groups thereof.

[0031] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which this application belongs. In addition, unless explicitly defined herein, terms such as those defined in general dictionaries should be interpreted as having a meaning consistent with their meaning in the relevant technology and the content of this application, and will not be interpreted as an idealized or overly formal meaning.

[0032] The specific implementation methods of the present application are further described in detail below with reference to the accompanying drawings.

[0033] The present invention provides a positive electrode material, the chemical formula of which is LiNi x Co y Mn z M i O 2 ; wherein x≥0, y≥0, Z≥0, i≥0, and x+y+z+i=1, and M includes one or more of Al, Zr, Ti, Mg, Sr, W, Y, Nb, Ca, Mo, B, F, Ge, Sn, Ce, and Ta. Moreover, the half-peak widths of the (003) crystal plane, (006) crystal plane, (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane, and (110) crystal plane of the positive electrode material should simultaneously satisfy their corresponding relationships.

[0034] In one embodiment, in the positive electrode material, after XRD testing, the half-peak widths of the (003) crystal plane and the (006) crystal plane of the positive electrode material are D n Each satisfies the formula 0.01n+0.067≥D n ≥0.053, the value of n is 1 or 2, wherein the value of n is 1 when corresponding to the (003) crystal plane of the positive electrode material, and the value of n is 2 when corresponding to the (006) crystal plane of the positive electrode material.

[0035] In one embodiment, in the positive electrode material, after XRD testing, the half-peak widths of the (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane of the positive electrode material are D n Each satisfies the formula 0.01n+0.067≥D n ≥0.01n+0.023, the value of n is 3 to 7 and n is an integer, wherein the value of n is 3 when corresponding to the (012) crystal plane of the positive electrode material, the value of n is 4 when corresponding to the (101) crystal plane of the positive electrode material, the value of n is 5 when corresponding to the (104) crystal plane of the positive electrode material, the value of n is 6 when corresponding to the (018) crystal plane of the positive electrode material, and the value of n is 7 when corresponding to the (110) crystal plane of the positive electrode material.

[0036] Or, it can be expressed as the half-peak width D of the crystal surface of the better positive electrode material nSatisfies formula 1:

[0037] Formula 1:

[0038] Among them, the corresponding relationship between the value of n and each crystal plane of the positive electrode material satisfies the following Table 1:

[0039] Table 1

[0040] Crystal face (003) (006) (012) (101) (104) (018) (110) The value of n 1 2 3 4 5 6 7

[0041] Furthermore, in the positive electrode material provided in the embodiment of the present application, the half-widths of the (003) crystal plane, (006) crystal plane, (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane are simultaneously constrained. This constraint condition is different from the half-width ratio constraint condition, and can avoid the disadvantage that the aforementioned ratio constraint condition cannot provide feedback on the overall situation of the crystal structure. At the same time, the short-term and long-term electrical properties of the positive electrode material corresponding to the embodiment of the present application are excellent.

[0042] It should be explained that in general technology, the material properties are controlled by controlling the crystal structure of the material, but the means of controlling the crystal structure is usually to control the ratio between the half-width of multiple key crystal planes in the crystal structure, that is, the constraint conditions in general technology are the aforementioned half-width ratio type constraints. However, if the prepared crystals are poorly developed, the half-width of each key crystal plane in the crystal structure may change in the same proportion, and the differences in the crystal structure will exist simultaneously or even in the same proportion on each key crystal plane, which will cause the aforementioned half-width ratio type constraints to reduce or even completely hide the differences in the crystal structure. Then the aforementioned half-width ratio type constraints are usually difficult to reveal the fact that the crystal structure is poorly developed. That is, by monitoring the aforementioned half-width ratio type constraints, it is impossible to achieve effective monitoring of the crystal structure. The positive electrode material provided in the embodiments of the present application constrains the half-widths of the (003) crystal plane, (006) crystal plane, (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane, thereby ensuring that both the short-term and long-term electrical properties of the positive electrode material are better.

[0043] It should be explained that the XRD test, i.e., the X-ray diffraction test, is an analytical technique widely used in the fields of materials science, chemistry, geology, etc. It performs X-ray diffraction on the material and analyzes its diffraction pattern to obtain information such as the composition of the material, the structure or morphology of the internal atoms or molecules. The main applications of the XRD test include, but are not limited to, crystal structure analysis, phase qualitative analysis, phase quantitative analysis, grain size analysis, and crystallinity analysis.

[0044] In one embodiment, after XRD testing, the half-peak widths of the (003) and (006) crystal planes of the positive electrode material are D n Each satisfies the formula 0.01n+0.057≥D n ≥0.063, the half-peak width of the (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane of the positive electrode material D n Each satisfies the formula 0.01n+0.057≥D n ≥0.01n+0.033.

[0045] Or, it can be expressed as the half-peak width D of the crystal surface of the better positive electrode material n Satisfies formula 2:

[0046] Formula 2:

[0047] Among them, the corresponding relationship between the value of n and each crystal plane of the positive electrode material satisfies the aforementioned Table 1.

[0048] It can be understood that the crystal structure of the positive electrode material that meets the constraints of the above formula 2 is better than the crystal structure of the positive electrode material that meets the constraints of the above formula 1. Therefore, the short-term electrical performance and long-term performance of the positive electrode material that meets the constraints of the above formula 2 are better.

[0049] In one embodiment, the physicochemical indicators of the positive electrode material satisfy the relationship: 1.5≤D50 / (TD*SSA)≤3.5, wherein D50 represents the median particle size, TD represents the tap density, and SSA represents the specific surface area.

[0050] It is understandable that the three physical and chemical indicators of median particle size (D50), tap density (TD), and specific surface area (SSA) can reflect the size particle grading of the positive electrode material, the particle size distribution after grading, the amount of fine powder, or the quality of the coating effect from the side. Among them, different size particle grading will affect the tap density (TD) and median particle size (D50), thereby affecting the DC resistance (DCR) and capacity; and the more fine powder and the worse the secondary sintering coating, the larger the corresponding data specific surface area (SSA), indicating that the worse the processing of the positive electrode material, the worse the cycle performance and storage performance, and the worse the high voltage performance. When the ratio of D50 / (TD*SSA) is between 1.5 and 3.5, the corresponding positive electrode material has better performance.

[0051] In one embodiment, the physicochemical indexes of the positive electrode material also satisfy the relationship: 10.5≤pH / (Li / M)≤11.5, wherein pH represents the acidity and Li / M represents the lithium metal ratio.

[0052] It is understandable that the two physicochemical indicators, pH and lithium metal ratio (Li / M), affect the processing performance, capacity and gas production performance of the material. Among them, the higher the pH, the greater the alkalinity of the material, and the easier it is to react with PVDF during slurry processing, causing a large rebound in slurry viscosity or even gelation. The lithium metal ratio (Li / M) will affect the pH level; among them, if the lithium metal ratio (Li / M) is too high, the alkalinity will increase, and the primary grains of the material will tend to be too large during the sintering process, resulting in poor uniformity of the primary grains and more serious lithium-nickel mixing; among them, if the lithium metal ratio (Li / M) is too low, the primary grains will not be fully developed, resulting in low capacity. When the pH / (Li / M) ratio is between 10.5 and 11.5, the corresponding positive electrode material has better performance.

[0053] like Figure 1 As shown, the present application embodiment also provides a method for preparing a positive electrode material, which is used to prepare the positive electrode material, and comprises the following steps:

[0054] Mixing a hydroxide precursor, a lithium source and an additive containing an M element to obtain a first mixed material;

[0055] The first mixed material is subjected to a first sintering process, and after the sintering process, it is subjected to a crushing and mixing process to obtain a second mixed material;

[0056] The second mixed material is sintered for a second time, and after sintering, crushed and mixed to obtain a third mixed material;

[0057] The third mixed material is sintered for a third time, and the positive electrode material is obtained by post-sintering treatment.

[0058] Furthermore, the preparation method of the positive electrode material provided in the embodiment of the present application realizes the control of the grain growth process by controlling the sintering process, thereby obtaining a stable crystal structure in which the half-width of each crystal plane meets the requirements, thereby obtaining a positive electrode material with better performance.

[0059] In one embodiment, the lithium metal ratio Li / M in the first mixed material ranges from 0.6 to 0.9.

[0060] In this embodiment, the lithium metal ratio Li / M in the first mixed material can specifically be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85 and 0.9.

[0061] In one embodiment, the hydroxide precursor may be a hydroxide containing nickel, cobalt, and manganese. x Co y Mn z (OH) 2, wherein x≥0, y≥0, Z≥0; the lithium source may be a lithium salt, such as lithium carbonate; the additive containing the element M may be a metal oxide corresponding to the element M, where M includes one or more of Al, Zr, Ti, Mg, Sr, W, Y, Nb, Ca, Mo, B, F, Ge, Sn, Ce, and Ta, and the additive containing the element M may be, for example, Al 2 O 3 etc.; the lithium source and the additive containing the M element can be general and feasible raw materials, which will not be elaborated here.

[0062] In one embodiment, the lithium metal ratio Li / M in the second mixed material ranges from 1.0 to 1.1.

[0063] In this embodiment, the lithium metal ratio Li / M in the second mixture can specifically be 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09 and 1.10.

[0064] In one embodiment, the aforementioned crushing and mixing treatment does not refer to a fixed processing process, but refers to a physical refining process such as jaw crushing, roller coarse crushing, air flow crushing, etc. on the mixture (the first mixture or the second mixture and its transition product), and a processing process in which a suitable mixer (such as a high-speed mixer) is used to mix the powders evenly to the extent that no white spots can be observed with the naked eye, which will not be elaborated here.

[0065] In one embodiment, during the first sintering process, the temperature is raised to the first platform temperature at a first heating rate, then kept at the temperature for a first time, and then naturally cooled to room temperature, and crushed and mixed to obtain the second mixture.

[0066] In one embodiment, the first heating rate ranges from 2° C. / min to 15° C. / min, the first platform temperature ranges from 700° C. to 820° C., and the first time ranges from 10 hours to 20 hours.

[0067] In this embodiment, the value of the first heating rate can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min and 15°C / min. The value of the first platform temperature can be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C and 820°C. The value of the first time can be 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours and 20 hours.

[0068] In one embodiment, during the second sintering process, the temperature is first increased to the second platform temperature at a second heating rate, then kept warm for a second time, then increased to the third platform temperature at a third heating rate, then kept warm for a third time, and after keeping warm, the temperature is cooled to the first transition temperature at the first cooling rate, and then naturally cooled to room temperature, and crushed and mixed to obtain a third mixture.

[0069] In one embodiment, the second heating rate ranges from 2°C / min to 15°C / min, the second platform temperature ranges from 700°C to 820°C, and the second time ranges from 3 hours to 10 hours; the third heating rate ranges from 2°C / min to 15°C / min, the third platform temperature ranges from 830°C to 1000°C, and the third time ranges from 8 hours to 15 hours; the first cooling rate ranges from 2°C / min to 10°C / min, and the first transition temperature is less than 300°C.

[0070] It can be understood by those skilled in the art that the temperature of the third platform temperature is related to the temperature of the hydroxide precursor Ni x Co y Mn z (OH) 2 The values ​​of x, y, and Z are relevant. For example, when x=0.6 (y=0.2 and z=0.2, or y=0.3 and z=0.1, or y=0.1 and z=0.3, or other satisfying ratios), the preferred range of the third platform temperature is 945°C to 970°C, and can further be 950°C to 960°C.

[0071] In this embodiment, the value of the second heating rate can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min and 15°C / min. The value of the second platform temperature can be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C and 820°C. The value of the second time can be 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours and 10 hours.

[0072] In this embodiment, the value of the third heating rate can be specifically 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min and 15°C / min. The value of the third platform temperature can be specifically 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C and 1000°C. The value of the third time can be specifically 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours and 15 hours.

[0073] In this embodiment, the value of the first cooling rate can specifically be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min and 10°C / min.

[0074] In one embodiment, during the third sintering process, the temperature is increased to a fourth platform temperature at a fourth heating rate, then kept at the temperature for a fourth time, and then naturally cooled to room temperature, and crushed and mixed to obtain the positive electrode material.

[0075] In one embodiment, the fourth heating rate ranges from 2° C. / min to 15° C. / min, the fourth platform temperature ranges from 300° C. to 800° C., and the fourth time ranges from 5 hours to 20 hours.

[0076] In this embodiment, the value of the fourth heating rate can be specifically 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min and 15°C / min. The value of the fourth platform temperature can be specifically 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C ℃ , 40 ℃, 550 ℃, 560 ℃, 570 ℃, 580 ℃, 590 ℃, 600 ℃, 610 ℃, 620 ℃, 630 ℃, 640 ℃, 650 ℃, 660 ℃, 670 ℃, 680 ℃, 690 ℃, 700 ℃, 710 ℃, 720 ℃, 730 ℃, 740 ℃, 750 ℃, 760 ℃, 770 ℃, 780 ℃, 790 ℃ and 800 ℃. The value of the fourth time can be specifically 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours and 20 hours.

[0077] The preparation method of the positive electrode material provided in the embodiment of the present application may include the following steps according to the preparation order:

[0078] Step S1: Mix the hydroxide precursor, lithium source, and one or more additives containing the M element using a high-speed mixer; wherein the lithium metal ratio (Li / M) is controlled to be in the range of 0.6 to 0.9. Mix evenly until no white spots are observed with the naked eye to obtain a first mixed material A1, and put the first mixed material A1 into a bowl and cut into pieces for later use.

[0079] Step S2: placing the sagger containing the first mixed material A1 in a sintering furnace for the first sintering, and introducing air or oxygen (the type and flow rate of the introduced gas are adaptively adjusted according to the type of synthetic material); heating to 700°C to 820°C at a temperature rate of 2°C / min to 15°C / min, and keeping the temperature for 10 to 20 hours; after the insulation is completed, cooling to room temperature by natural cooling to obtain the first sintering material B1.

[0080] Step S3: The first sintered material B1 is subjected to jaw crushing and roller crushing in sequence to obtain a first crushed material C1.

[0081] Step S4: The first crushed material C1, the lithium source, and one or more additives containing the M element are mixed in a high-speed mixer in an appropriate proportion; wherein, the lithium metal ratio (Li / M) of the first sintered material B1 is 0.6 to 0.9, and the lithium metal ratio (Li / M) of the new mixed material is increased to 1.0 to 1.1. The mixture is uniformly mixed to a degree where no white spots can be observed with the naked eye, and the second mixed material A2 is obtained, and the second mixed material A2 is potted and cut into pieces for later use.

[0082] Step S5: placing the sagger containing the second mixed material A2 into a sintering furnace for a second sintering, and introducing air or oxygen (the type and flow rate of the introduced gas are adaptively adjusted according to the type of synthetic material); firstly heating the mixture to 700°C to 820°C at a temperature rate of 2°C / min to 15°C / min, and keeping the temperature for 3 hours to 10 hours, then heating the mixture to 830°C to 1000°C at a temperature rate of 2°C / min to 15°C / min, and keeping the temperature for 8 hours to 15 hours, then cooling the mixture to no more than 300°C at a temperature reduction rate of 2°C / min to 10°C / min, and naturally cooling the mixture to room temperature after the temperature reduction is completed to obtain a second sintering material B2.

[0083] Step S6: The second sintered material B2 is subjected to jaw crushing, roller coarse crushing and air flow crushing in sequence to obtain a second crushed material C2.

[0084] Step S7: The second crushed material C2 and one or more additives containing the M element are mixed in a suitable proportion using a high-speed mixer. The crushed material and the additive are mixed evenly to a degree where no white spots can be observed with the naked eye to obtain a third mixed material A3. The mixed material is potted and cut into pieces.

[0085] Step S8: placing the sagger containing the third mixed material A3 in a sintering furnace for the third sintering, and introducing air or oxygen (the type and flow rate of the introduced gas are adaptively adjusted according to the type of synthetic material); heating to 300° C. to 800° C. at a temperature rate of 2° C. / min to 15° C. / min, and keeping the temperature for 5 hours to 20 hours; after the insulation is completed, cooling to room temperature by natural cooling to obtain a third sintered material B3.

[0086] Step S9: The third sintered material B3 is dispersed and processed successively to obtain a third crushed material C3, which is sieved and demagnetized to obtain a material mainly containing LiNi x Co y Mn z M i O 2 The positive electrode material can be tested later.

[0087] The present application also provides a number of specific embodiments and comparative examples based on the aforementioned embodiments, which are shown as follows:

[0088] Example 1

[0089] Step S11: Using Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 Precursor, add Li at a ratio of Li / M = 0.85 2 CO 3 (lithium salt), the additive containing M element is ZrO 2 , add Zr element at a ratio of 2000ppm, use a high-speed mixer to mix evenly until no white spots can be observed with the naked eye, obtain the first mixed material A1, put it into a bowl, and cut it into pieces.

[0090] Step S12: placing the sagger containing the first mixed material A1 into a sintering furnace, introducing air, heating the furnace to a first platform temperature of 780°C at a heating rate of 8°C / min, and keeping the temperature for 18 hours. After the temperature is kept, the sagger is naturally cooled to room temperature to obtain a first sintering material B1.

[0091] Step S13: The first sintered material B1 is subjected to jaw crushing and roller crushing to obtain a first crushed material C1;

[0092] Step S14: First crushed material C1, Li 2 CO 3 (lithium salt), Al 2 O 3 (Additives containing element M) are mixed using a high-speed mixer, wherein lithium is added to increase the Li / M to 1.05 based on the Li / M=0.85 of the first crushed material C1, and Al element is added at a ratio of 1500ppm. The mixture is evenly mixed to a level where no white spots can be observed with the naked eye, to obtain a second mixed material A2, which is then filled into a bowl and cut into pieces.

[0093] Step S15: Place the sagger containing the second mixed material A2 into the sintering furnace and introduce air. First, heat it to the second platform temperature of 820°C at a heating rate of 10°C / min and keep it warm for 5 hours. Then heat it to the third platform temperature of 950°C at a heating rate of 8°C / min and keep it warm for 10 hours. After the insulation is completed, cool it to below 300°C at a cooling rate of 5°C / min. After the cooling is completed, naturally cool it to room temperature to obtain the second sintering material B2.

[0094] Step S16: The second sintered material B2 is subjected to jaw crushing, roller crushing and air flow crushing in sequence to obtain a second crushed material C2.

[0095] Step S17: The second crushed materials C2 and W 2 O 3The (M-containing additive) was mixed using a high-speed mixer, wherein the W element was added at a ratio of 1500 ppm, and mixed evenly until no white spots were detected by the naked eye, to obtain the third mixed material A3, which was then put into a bowl and cut into pieces.

[0096] Step S18: placing the sagger containing the third mixed material A3 into a sintering furnace, introducing air, heating to 400°C at a heating rate of 10°C / min, and keeping the temperature for 15 hours. After the heat preservation, naturally cooling to room temperature, and obtaining the third sintered material B3.

[0097] Step S19: The third sintering material B3 is dispersed to obtain the third crushed material C3, which is then sieved and demagnetized to complete the LiNi 0.6 Co 0.1 Mn 0.3 MiO 2 Preparation of positive electrode materials and related tests.

[0098] Example 2

[0099] The difference between Example 2 and Example 1 is that the temperature of the third platform in step S15 of Example 2 is increased to 960° C. compared with that of Example 1.

[0100] Example 3

[0101] The difference between Example 3 and Example 1 is that the holding time of the third platform temperature in step S15 of Example 3 is reduced to 8 hours compared with that of Example 1.

[0102] Example 4

[0103] The difference between Example 4 and Example 1 is that the insulation time of the third platform temperature in step S15 of Example 4 is increased to 12 hours compared with that of Example 1.

[0104] Example 5

[0105] The difference between Example 5 and Example 1 is that the M-containing additive before the second sintering in step S14 of Example 5 is increased by SrO, and the added amount of Sr is 500 ppm.

[0106] Comparative Example 1

[0107] The difference between Comparative Example 1 and Example 1 is that the temperature of the third platform in step S15 of Comparative Example 1 is lowered to 930° C. compared with that of Example 1.

[0108] Comparative Example 2

[0109] The difference between Comparative Example 2 and Example 1 is that in step S15 of Comparative Example 2, the sagger containing the second mixed material A2 is placed in a sintering furnace, and air is introduced, and the temperature is increased to 950°C at a heating rate of 10°C / min and kept warm for 10 hours. After the insulation is completed, it is naturally cooled to room temperature to obtain a second sintered material B2.

[0110] The positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to XRD test, charge-discharge test and DSC test. The results are as follows: Figure 2 And the following table 2:

[0111] Table 2

[0112]

[0113] It needs to be explained that Figure 2 The better boundary at the upper side corresponds to Y1=0.01X+0.067, and the better boundary at the lower side corresponds to Y2=0.01X+0.023, wherein X represents the horizontal axis, and Y1 and Y2 represent the vertical axes. Figure 2 The better boundary on the upper side corresponds to Y1=0.01X+0.057, and the better boundary on the lower side corresponds to Y2=0.01X+0.033, wherein X represents the horizontal axis, and Y1 and Y2 represent the vertical axes.

[0114] Combination Figure 2 From Table 2, we can see that:

[0115] For Example 1: The key physical and chemical indicators of Example 1 are within the required range, and the half-peak width of each crystal plane is within the optimal boundary range, and its comprehensive performance is the best among all the examples and comparative examples.

[0116] For Example 2: Compared with Example 1, the key parameter D50 / (TD*SSA) of Example 2 is slightly lower, and the pH / (Li / M) is not much different, which is generally within the required range. The half-peak width of the (101) crystal plane is on the better lower boundary but within the better boundary, which has little effect on the capacity. The half-peak width of other crystal planes is within the better boundary, and the half-peak width of the crystal plane does not exceed the better boundary as a whole. The comprehensive performance of the material is comparable to that of Example 1.

[0117] For Example 3: Compared with Example 1, the key parameters D50 / (TD*SSA) and pH / (Li / M) of Example 3 are not much different, and the overall is within the required range. The half-peak width of the (110) crystal plane is outside the better boundary but within the better boundary, and the half-peak width of the other crystal planes is within the better boundary. Although the cycle performance of the material is slightly inferior to that of Example 1, the retention rate is still good.

[0118] For Example 4: Compared with Example 1, the key parameter D50 / (TD*SSA) of Example 4 is slightly increased, and the pH / (Li / M) is not much different, which is generally within the required range. The half-peak width of the (003) crystal plane is outside the better boundary but within the better boundary, and the half-peak widths of the other crystal planes are all within the better boundary. Although the capacity of the material is slightly less than that of Example 1, the overall performance is still good.

[0119] For Example 5: Compared with Example 1, the key parameter D50 / (TD*SSA) of Example 5 increased significantly, and pH / (Li / M) was not much different, which was generally within the required range. The half-peak widths of the (003) crystal plane, (012) crystal plane, and (018) crystal plane were within the more optimal boundary, and the half-peak widths of the other crystal planes were outside the more optimal boundary but within the better boundary. Although the capacity and DSC results of the material were not as good as those of Example 1, the overall performance was still good.

[0120] For Comparative Example 1: Compared with Example 1, the key parameter D50 / (TD*SSA) of Comparative Example 1 is significantly reduced, and the pH / (Li / M) is not much different, which is generally within the required range. However, the half-peak width of most crystal faces of Comparative Example 1 is outside the optimal boundary, and the capacity, cycle performance and DSC test of the material are all poor.

[0121] It should be explained that, although the third platform temperature 930°C in step S15 of comparative example 1 is within the range of 830°C to 1000°C, the range of 830°C to 1000°C is for the hydroxide precursor Ni x Co y Mn z (OH) 2 The values ​​of x, y, and Z are comprehensively varied to set a reasonable wide range; the hydroxide precursor in Comparative Example 1 is Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 The corresponding third platform temperature preferably ranges from 945°C to 970°C, and can further range from 950°C to 960°C. The third platform temperature of 930°C in Comparative Example 1 is not within this range and is much lower, resulting in poor grain growth in Comparative Example 1.

[0122] For Comparative Example 2: Compared with Example 1, the key parameters D50 / (TD*SSA) and pH / (Li / M) of Comparative Example 2 are not much different, and the overall is within the required range. The half-peak width of the (110) crystal plane is outside the optimal boundary, resulting in poor cycling performance and DSC results of the material.

[0123] Based on the above results, the positive electrode material prepared in the embodiment of the present application has the best comprehensive performance in terms of key physical and chemical indicators and the half-peak width of each crystal plane within a more optimal boundary.

[0124] An embodiment of the present application also provides a positive electrode plate, which includes a positive electrode material, wherein the positive electrode material is the positive electrode material of any one of the aforementioned embodiments, or the positive electrode material is prepared by the preparation method of the positive electrode material of any one of the aforementioned embodiments.

[0125] It can be understood that, in addition to the positive electrode material, the positive electrode plate may also include other auxiliary materials used to form the positive electrode plate, such as a binder, etc., which will not be elaborated here.

[0126] An embodiment of the present application also provides a battery, which includes the positive electrode plate as described in the above embodiment.

[0127] It is understandable that, in addition to the positive electrode plate, the battery may also include other materials or structures that constitute the battery, such as an isolation membrane, an electrolyte, a protective shell, a power management component, etc., which will not be elaborated here.

[0128] The embodiment of the present application further provides an electricity-consuming device, which includes an electricity-consuming body and a battery as described in the above embodiment, wherein the battery is electrically connected to the electricity-consuming body.

[0129] It can be understood that the power-consuming device can be an electric vehicle or a hybrid vehicle, and the power-consuming entity can include other structures in the electric vehicle or hybrid vehicle except the battery, such as the body, motor, engine, transmission system, detection system, etc., which will not be elaborated here.

[0130] Furthermore, the positive electrode plate, battery and electrical device provided in the embodiments of the present application all use the positive electrode material, and both the short-term and long-term electrical properties are excellent.

[0131] In the above, the specific embodiments of the present application are described with reference to the accompanying drawings. However, those skilled in the art will appreciate that various changes and substitutions may be made to the specific embodiments of the present application without departing from the scope of the present application. These changes and substitutions are all within the scope defined by the present application.

Claims

1. A positive electrode material, characterized in that: The chemical formula of the positive electrode material is LiNi x Co y Mn z M i O2; Wherein, x≥0, y≥0, Z≥0, i≥0, and x+y+z+i=1, and M includes one or more of Al, Zr, Ti, Mg, Sr, W, Y, Nb, Ca, Mo, B, F, Ge, Sn, Ce, and Ta; In the positive electrode material, the half-peak width of the (003) crystal plane and the (006) crystal plane of the positive electrode material is D n Each satisfies the formula 0.01n+0.067≥D n ≥0.053, the value of n is 1 or 2, wherein the value of n is 1 when corresponding to the (003) crystal plane of the positive electrode material, and the value of n is 2 when corresponding to the (006) crystal plane of the positive electrode material; In the positive electrode material, the half-peak widths of the (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane of the positive electrode material are D n Each satisfies the formula 0.01n+0.067≥D n ≥0.01n+0.023, the value of n is 3 to 7 and n is an integer, wherein the value of n is 3 when corresponding to the (012) crystal plane of the positive electrode material, the value of n is 4 when corresponding to the (101) crystal plane of the positive electrode material, the value of n is 5 when corresponding to the (104) crystal plane of the positive electrode material, the value of n is 6 when corresponding to the (018) crystal plane of the positive electrode material, and the value of n is 7 when corresponding to the (110) crystal plane of the positive electrode material.

2. The positive electrode material according to claim 1, characterized in that The half-peak width of the (003) crystal plane and the (006) crystal plane of the positive electrode material is D n Each satisfies the formula 0.01n+0.057≥D n ≥0.063, the half-peak widths of the (012) crystal plane, (101) crystal plane, (104) crystal plane, (018) crystal plane and (110) crystal plane of the positive electrode material are D n Each satisfies the formula 0.01n+0.057≥D n ≥0.01n+0.

033.

3. The positive electrode material according to claim 1, characterized in that The physicochemical indicators of the positive electrode material satisfy the relationship: 1.5≤D50 / (TD*SSA)≤3.5, wherein D50 represents the median particle size, TD represents the tap density, and SSA represents the specific surface area.

4. The positive electrode material according to claim 1, characterized in that The physicochemical indexes of the positive electrode material satisfy the relationship: 10.5≤pH / (Li / M)≤11.5, wherein pH represents the acidity and Li / M represents the lithium metal ratio.

5. A method for preparing a positive electrode material, characterized in that: The method for preparing the positive electrode material is used to prepare the positive electrode material according to any one of claims 1 to 4, and the method for preparing the positive electrode material comprises the following steps: Mixing a hydroxide precursor, a lithium source and an additive containing an M element to obtain a first mixed material; The first mixed material is subjected to a first sintering process, and after the sintering process, it is subjected to a crushing and mixing process to obtain a second mixed material; The second mixed material is sintered for a second time, and after sintering, crushed and mixed to obtain a third mixed material; The third mixed material is sintered for a third time, and the positive electrode material is obtained by post-sintering treatment.

6. The method for preparing the positive electrode material according to claim 5, characterized in that: During the first sintering process, the temperature is raised to the first platform temperature at a first heating rate, then kept at the temperature for a first time, and then naturally cooled to room temperature after the holding time, and crushed and mixed to obtain the second mixed material; During the second sintering process, the temperature is first increased to the second platform temperature at a second heating rate, then kept at the temperature for a second time, then increased to the third platform temperature at a third heating rate, then kept at the temperature for a third time, and after keeping at the temperature, the temperature is cooled to the first transition temperature at the first cooling rate, and then naturally cooled to room temperature, and crushed and mixed to obtain the third mixed material; During the third sintering process, the temperature is raised to a fourth platform temperature at a fourth heating rate, then kept at the temperature for a fourth time, and then naturally cooled to room temperature, and crushed and mixed to obtain the positive electrode material.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: The first heating rate ranges from 2°C / min to 15°C / min, the first platform temperature ranges from 700°C to 820°C, and the first time ranges from 10 hours to 20 hours; The second heating rate ranges from 2°C / min to 15°C / min, the second platform temperature is 700°C to 820°C, the second time is 3 hours to 10 hours, the third heating rate ranges from 2°C / min to 15°C / min, the third platform temperature is 830°C to 1000°C, the third time is 8 hours to 15 hours, the first cooling rate ranges from 2°C / min to 10°C / min, and the first transition temperature is less than 300°C; The fourth heating rate ranges from 2°C / min to 15°C / min, the fourth platform temperature ranges from 300°C to 800°C, and the fourth time ranges from 5 hours to 20 hours.

8. The method for preparing the positive electrode material according to claim 5, characterized in that: The lithium metal ratio Li / M in the first mixture ranges from 0.6 to 0.9, and the lithium metal ratio Li / M in the second mixture ranges from 1.0 to 1.

1.

9. A positive electrode sheet, characterized in that: It includes the positive electrode material, wherein the positive electrode material is the positive electrode material described in any one of claims 1 to 4, or the positive electrode material is prepared by the preparation method of the positive electrode material described in any one of claims 5 to 8.

10. A battery, characterized in that: Comprising the positive electrode sheet as described in claim 9.

11. An electrical device, characterized in that: The invention comprises an electricity-consuming subject and the battery as claimed in claim 10, wherein the battery is electrically connected to the electricity-consuming subject.